2019
DOI: 10.1111/tri.13389
|View full text |Cite
|
Sign up to set email alerts
|

For the many: permitting deceased donor kidney transplantation across low‐titre blood group antibodies can reduce wait times for blood group B recipients, and improve the overall number of 000MMtransplants ‐ a multicentre observational cohort study

Abstract: Summary Blood group O or B recipients wait longer for a kidney transplant. We studied the distribution of anti‐ABO blood group antibody titres in patients awaiting a kidney transplant, and modelled the effect of altering the UK National Kidney Allocation Scheme to allow for patients with ‘LOW’ titres (≤1:8, ≤3 dilutions) to receive a deceased donor ABOi (ddABOi) transplant. In a prospective study of 239 adult patients on the waiting list for a transplant in 2 UK centres, ABO‐antibody titres (anti‐A and anti‐B)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…To promote ABOi KTx, the Chinese Society of Organ Transplantation and Chinese Transplant Doctor Association published the Clinical Guideline for ABO-Incompatible Living-Donor Kidney Transplantation in 2017 [29]. Although more cases are required for further refinement of these protocols, the main findings of our research are that the use of personalized protocols allows a wider range of patients to benefit from ABOi transplantation, especially those with low initial titers [26].…”
Section: Discussionmentioning
confidence: 98%
“…To promote ABOi KTx, the Chinese Society of Organ Transplantation and Chinese Transplant Doctor Association published the Clinical Guideline for ABO-Incompatible Living-Donor Kidney Transplantation in 2017 [29]. Although more cases are required for further refinement of these protocols, the main findings of our research are that the use of personalized protocols allows a wider range of patients to benefit from ABOi transplantation, especially those with low initial titers [26].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, previous studies have shown persistent disparity in organ allocation due to ABO incompatibility. In this context, blood group B and O kidney transplant candidates face additional barriers to transplantation than those with blood types A and AB, resulting in a longer waitlist time and accumulation of candidates on the waitlist 19–23 . Blood group O candidates are only biologically compatible with blood group O donor, whereas blood group O donors are compatible with candidates of all blood group.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, blood group B and O kidney transplant candidates face additional barriers to transplantation than those with blood types A and AB, resulting in a longer waitlist time and accumulation of candidates on the waitlist. [19][20][21][22][23] Blood group O candidates are only biologically compatible with blood group O donor, whereas blood group O donors are compatible with candidates of all blood group. Zero HLA-A, B, DR mismatch donors' kidney might be allocated to potential recipients who belong to other compatible blood groups.…”
mentioning
confidence: 99%
“…13 KT across the A2 barrier (A2 → O, A2 → B, A2B → B) is believed to be safer than that across the A1 barrier (A1 → O, A1 → B, A1B → B) because A2 kidneys express fewer A antigens on their renal endothelial surfaces. 4,5,14 The Organ Procurement and Transplantation Network (OPTN) introduced a voluntary variance in 2002, allowing A2 and A2B kidneys to be allocated to type B recipients. 2 In 2014, A2-incompatible (A2i) became part of the standard allocation system under the Kidney Allocation System (KAS), provided a certain center-specific anti-A 2 titer threshold was met.…”
mentioning
confidence: 99%
“…
A BO type B and O kidney transplant (KT) candidates experience greater barriers to transplantation than type A and AB candidates, due to decreased chances of ABO compatibility. [1][2][3][4][5][6][7] Type B and O candidates combined represented 70.1% of the kidney waitlist in July 2022 and 63.5% of waitlist additions between January 1995 and June 2022. Type B and O donors, however, represented just 59.4% of deceased donors in 2021.
…”
mentioning
confidence: 99%